Biogenic Synthesis and Characterization of Antimicrobial and Antiparasitic Zinc Oxide (ZnO) Nanoparticles Using Aqueous Extracts of the Himalayan Columbine (Aquilegia pubiflora) - Jan, Hasnain; Shah, Muzamil; Usman, Hazrat; Khan, Muhammad Aslam; Zia, Muhammad; Hano, Christophe; Abbasi, Bilal Haider (Frontiers in Materials, 2020)
Herein, we report a facile, economic, one-pot green synthesis of Zinc Oxide nanoparticles (ZnO-NPs) for diverse biomedical applications. In the study, ZnO-NPs were synthesized using an aqueous extract of Aquilegia Publifora as an effective reducing and capping agent. The bio mediated nanoparticles were characterized using various techniques like HPLC, XRD, FTIR, SEM, DLS, PL and RAMAN. The particles were highly pure, having an average size of 34. 23nm with spherical or elliptical shaped morphology and displayed good aqueous dispersion capability. FTIR and HPLC confirmed the successful capping of flavonoids and hydroxycinnamic acid derivatives. The characterized NPs were then explored for their antimicrobial and antileishmanial potential. Among the tested bacterial and fungal strains, ZnO-NPs were most potent towards Pseudomonas aeruginosa and Fusarium solani with inhibition zone of 10.3±0.19 mm and 13±1.4 mm, respectively. In addition, bacterial kinase enzymes were inhibited by ZnO-NPs, thus allowing us to elaborate a possible action mechanism. Moreover, a dose-dependent cytotoxic effect was observed against Leishmania tropica (KWH23) with significant IC50 for both the promastigote (48 μg/mL) and amastigote form (51 μg/mL) of the parasite. Finally, the notable biocompatible nature of the particles was confirmed against freshly isolated human red blood cells (hRBCs). All together these results affirmed the high antimicrobial and anti-parasitic potential of ZnO-NPs obtained through biogenic synthetic approach using aqueous extract of the Himalayan Columbine (Aquilegia Publifora).